The point-slope form of the equation for a line can be written as
... y = m(x -h) +k . . . . . . . for a line with slope m through point (h, k)
Your function gives
... f'(h) = m
... f(h) = k
a) The tangent line is then
... y = 5(x -2) +3
b) The normal line will have a slope that is the negative reciprocal of that of the tangent line.
... y = (-1/5)(x -2) +3
_____
You asked for "an equation." That's what is provided above. Each can be rearranged to whatever form you like.
In standard form, the tangent line's equation is 5x -y = 7. The normal line's equation is x +5y = 17.
Answer:
y is less than -2x+3
Step-by-step explanation:
Answer:708
Step-by-step explanation:
Answer:
(7x-1)(x-3)
Step-by-step explanation:
7x^2 - 22x + 3
The factors have to add to -22, but multiply to equal 3. But since the "a" value has a number on it, you have to use it too.
(7x +/- [n1]) ( x +/- [n2]) = 7x^2 - 22x + 3
Since the two numbers multiply to a positive value, they have to have the same sign. (7x-1) (x-3) works to produce the expression when it's foiled.